Successful farming ventures for prosperity in arid zone - Singh, Dheeraj; Choudhary, M. K.; Sharma, S. K.; Dayal, Devi; Yadav, O. P. (Indian Farming, 2018)
The farming in arid regions is very challenging and risk-prone due to climatic stresses and poor economic conditions of communities. Farmers are mainly engaged in subsistence farming. With the small technological interventions and appropriate training and capacity building of farmers coupled with innovations, not only risk can be minimized but income of farmers can also be enhanced. The successful examples presented in this paper showed how innovations of individual farmers serve as inspiration for others in communities ultimately leading to transformation of their social life.